Is Amorality the Sixth Factor of Personality? - Međedović, Janko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
The aim of this study was to determine the status of the psychological concept of Amorality. The hypothesis, which was tested in the research, is based on the assumption of Amorality as a personality trait that generates stable behaviours that can result in violation of moral codes, social norms, manipulation and criminality. In the revised lexical model of personality (HEXACO model), a broad personality trait that was not described in the previous operationalisations was isolated: Honesty - Humility. This dimension is described by traits such as integrity, honesty, sense of fair play, loyalty and humility, as opposed to fickleness, hypocrisy, arrogance, greed and cunning. Based on this definition of the Honesty factor, we set a hypothesis that the core of amoral dispositions is located at its negative pole, which means that Amorality is the aspect of dishonesty, as a basic personality trait. To test this hypothesis, an exploratory principal components analysis in the shared space of Amorality and HEXACO personality traits was performed, and a structural model that describes the causal relationships between personality traits and Amorality was constructed. Data was collected in a sample that consisted of 229 students of the first and second year of the University of Belgrade and Singidunum University (65% girls). Both analyses confirmed the initial hypothesis: Amorality generated by Frustration and Amorality generated by Brutality are the personality traits associated with the negative pole of Honesty - humility, while benign forms of Amorality (Amorality generated by Impulsivity) are an expression of low Conscientiousness. In order to determine the predictive utility of Amorality, a hierarchical linear regression with subclinical psychopathy as a criterion was conducted. Basic personality traits were set as predictors on the first level, and Amorality factors were set as predictors at the second level of the analysis. The results show that there is a significant contribution of the Amorality in the prediction, above and beyond HEXACO traits, when it comes to all four aspects of psychopathy as a criterion.